KINERJA KEUANGAN PT. KERSA GUNUNG WASADA - -, Beti Darnawati (EKONOMIA, 2014)
The development of an enterprise can be seen from the financial statements, from year to year or from one period to the next period. Financial Budget and Cost Advantages reflected in the financial statements, financial statements in which it is a picture of a company's ability liabilities (long term and short term) to be met. But PT Kersa Gunung Wasada not know how much strength and weaknesses as well as the possibility of expanding its business when viewed in terms financialnya because the company has not been analyzed keuanganya reports using appropriate financial ratios. Based on this background, the problems in this thesis is